Strategi Manajemen Humas dalam Meningkatkan Animo Masyarakat terhadap Pendidikan Madrasah - Hakim, Muhammad Nur; Rozi, Fahrur (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
This study aims to analyze and compare public relations management strategies at MAN Gondanglegi and MA AN-Nur Bululawang, with a focus on enhancing community interest in these educational institutions. Employing a qualitative approach, this research scrutinizes planning, execution, and evaluation phases of public relations within both schools, alongside their impact on attracting more students. Results demonstrate that both MAN Gondanglegi and MA AN-Nur Bululawang employ a comprehensive array of strategies, including media publications, alumni networks, and community engagement activities, which have significantly increased their popularity and student enrollment. The study concludes that effective public relations management plays a crucial role in the growth and reputation of educational institutions. These findings underline the importance of strategic communication and community involvement in the educational sector, offering valuable insights for other institutions aiming to enhance their public image and attract more students. For further research, it is recommended that researchers conduct a more in-depth analysis of the long-term impact of public relations management strategies on improving the image and reputation of educational institutions at national and international levels.